2015
DOI: 10.1016/j.eja.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Propensity for seed-mediated gene flow from potato crops and potential consequences for the coexistence of GM and non-GM potato systems

Abstract: Potato is a critical crop to European growers, both economically and agronomically as a break crop in the standard cereal rotation. As studies investigating the agronomic performance and environmental impact of disease resistant, GM potatoes come to an end across several sites in Europe, past discussions on achieving the effective coexistence of GM and equivalent non-GM crops have too often focussed on the purported risk of excessive pollen-mediated gene flow. Dependent on the crop in question, the impact of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Other publications report figures from 180 000 up to 460 000 tubers per hectare remaining on a field after harvest (Lumkes, 1974;Perombelon, 1975;Lutman, 1977;Steiner et al, 2005;Boydston et al, 2006). More recently, Phelan et al (2015) reported an average tuber loss of 142 000 tubers per hectare, ranging from about 39 000 to 210 000 tubers. Not all tubers produce plants that survive to the following crop.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other publications report figures from 180 000 up to 460 000 tubers per hectare remaining on a field after harvest (Lumkes, 1974;Perombelon, 1975;Lutman, 1977;Steiner et al, 2005;Boydston et al, 2006). More recently, Phelan et al (2015) reported an average tuber loss of 142 000 tubers per hectare, ranging from about 39 000 to 210 000 tubers. Not all tubers produce plants that survive to the following crop.…”
Section: Introductionmentioning
confidence: 97%
“…More recently, Phelan et al . (2015) reported an average tuber loss of 142 000 tubers per hectare, ranging from about 39 000 to 210 000 tubers. Not all tubers produce plants that survive to the following crop.…”
Section: Introductionmentioning
confidence: 99%